Asymptotic formula in simultaneous approximation for certain Ismail-May-Baskakov operators - Gupta, Vijay; Rassias, Michael Th. (J. Numer. Anal. Approx. Theory, 2021)
In the present paper, we introduce a modification of Ismail-May operators having weights of Baskakov basis functions. We estimate weighted Korovkin’s theorem and difference estimates between two operators and establish a Voronovskaja type asymptotic formula in simultaneous approximation.